2014
DOI: 10.1590/1981-8637201400010000092623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pH and titratable acidity of teas commercially available in Brazilian market

Abstract: Objective Tea has been considered a healthy alternative to other industrialized beverages. The objective of this study was to assess the erosive potential of teas commercially available in Brazil by pH and titratable acidity measures. Methods Eighteen teas available in RESUMO ObjetivoAvaliar o potencial erosivo de chás comercialmente disponíveis no mercado brasileiro através da avaliação dos valores de pH e de titrabilidade ácida. MétodosForam selecionados dezoito chás disponíveis no mercado brasileiro (pronto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
(27 reference statements)
2
10
1
1
Order By: Relevance
“…ere were statistical differences (p < 0.05) between tea samples in physicochemical parameters ( e results of the present study show higher pH values than data reported by Lunkes and Hashizume [19], whom analyzed 11 commercial ready-to-drink flavored teas available in Brazil market and found pH values ranging from 2.89 to 3.41. In addition, the titratable acidity reported by these authors was higher than our observations, since they found values ranging from 0.193 to 0.325%.…”
Section: Physicochemical Parameterscontrasting
confidence: 68%
“…ere were statistical differences (p < 0.05) between tea samples in physicochemical parameters ( e results of the present study show higher pH values than data reported by Lunkes and Hashizume [19], whom analyzed 11 commercial ready-to-drink flavored teas available in Brazil market and found pH values ranging from 2.89 to 3.41. In addition, the titratable acidity reported by these authors was higher than our observations, since they found values ranging from 0.193 to 0.325%.…”
Section: Physicochemical Parameterscontrasting
confidence: 68%
“…The pH of the samples was measured using pH-meter according to the method used by [14], with some few modifications. Five grams (5 g) of previously weighed sample was dissolved in 25 mL distilled water and homogenized until particles were evenly suspended with mixture free of lumps.…”
Section: Phmentioning
confidence: 99%
“…O alto consumo de bebidas e alimentos ácidos representam fatores extrínsecos relevantes para o desenvolvimento desta patologia dentária (LUSSI et al, 2012;LUNKES;HASHIZUME, 2014). A modificação no estilo de vida tem contribuído para o aumento da quantidade e da frequência de consumo de produtos ácidos (LUSSI et al, 2012).…”
Section: Discussionunclassified